Multicomponent Syntheses to Alkene- and Alkyne-Functionalized Benzopyrans via Alkynylation and [4+2] Cyclization in One-Pot Process - Shao, Jidong; Li, Liqi; Zhang, Jie; Tian, Tian; Xue, Jijun; Zhang, Yuan; Li, Ying (Synlett, 2015)
A novel multicomponent synthesis was found to be an efficient and elegant approach to 2,4-difunctionalized benzopyrans. This sequence includes ZnMe2-promoted alkynylation of salicylaldehyde and ZnCl2-mediated [4+2] cyclization proceeding in sequence of a one-pot process, providing a series of benzopyrans with good diastereoselectivities and moderate yields (dr 20:1 to 4:1). These products are potential precursors and bioactive core skeletons of natural products.
Keywords: one-pot; multicomponent; alkynylation; [4+2] cyclization; benzopyran